Hydrogen breath test as a diagnostic tool - Zozula, Natalia; Tomczewska, Zuzanna; Rykucka, Aleksandra; Wąs, Marcin; Latała, Aleksandra; Kiełbasa, Justyna; Kowalczyk, Agata; Bil, Katarzyna; Ślesicka, Iga; Przestrzelska, Magda (Quality in Sport, 2024)
Introduction and Purpose: Hydrogen breath tests serve the crucial purpose of evaluating the absorption of nutrients in the small intestine, particularly when carbohydrates are not properly absorbed, leading to bacterial overgrowth. These tests are non-invasive, cost-effective, and widely accessible diagnostic tools used to assess various gastrointestinal disorders. The objective of this review is to evaluate the effectiveness and methodology of Hydrogen breath testing (HBT). State of knowledge: The disposal of hydrogen gas is essential for maintaining efficient microbial fermentation processes in the gut. Hydrogenotrophic microbes, including acetogens, methanogenic archaea, and sulfate-reducing bacteria, are responsible for this process. Hydrogen breath tests, conducted with substrates like glucose and lactulose, aid in diagnosing conditions such as small intestinal bacterial overgrowth (SIBO), lactose and fructose intolerance, and other carbohydrate absorption disorders. These tests generate a large volume of data, which can be analyzed using data mining techniques to uncover new hypotheses. Conclusions: Hydrogen breath tests, using various substrates, are effective in diagnosing gastrointestinal disorders such as SIBO and carbohydrate malabsorption. They offer valuable insights into microbial processes in the gut and can inform individualized treatment strategies. However, careful consideration of contraindications and proper test administration protocols is essential for accurate diagnosis and interpretation of results.